Exploring the effects of energy consumption on millets and rice yields in Odisha, India - Diptimayee Jena; Bamadev Mahapatra (Energy Nexus, 2023)
Energy is a crucial input in determining the agricultural growth of an economy. Thus, this study aims to investigate the impact of energy consumption (EC) on agricultural productivity growth (APG), specifically in relation to rice and millet yields in Odisha, India. The study uses data from the period spanning 1990–91 to 2019–20. The study uses an autoregressive distributed lag (ARDL) bound F-test to examine for a cointegration relationship amid the variables, and an ARDL regression framework to investigate the effect of EC on the yields of rice and millets in Odisha. The results advocate that there exists a long-run equilibrium relationship amid the variables in the study. Regarding the result for long- and short-run elasticities, it is evidenced that EC has a positive and statistically significant effect on rice yield and has no statistically significant impact on millet yield in the long-run. However, in the short-run, EC has a positive and statistically significant effect on both rice and millet yields. According to the findings of the current study, the state government of Odisha should place a greater emphasis on ensuring that farmers have access to power in order to encourage agricultural expansion and improve crop yields.